Simulation of Respiratory Distress for the Pediatrics Clerkship - Michael Sean Ryan (Association of American Medical Colleges, 2012)
Abstract A core competency of medical student education in pediatrics is for students to successfully identify and treat a child suffering from acute respiratory distress. Depending on seasonality, patient volumes, and available venues, it can be difficult to guarantee this experience to each student on the core pediatrics clerkship. While there are several resources for teaching skills using simulation (e.g., intubation, intravenous line placement), there is a paucity of resources using simulation to teach and assess clinical reasoning skills, particularly in medical students. Created to address these issues by taking into consideration the Council on Medical Student Education in Pediatrics' curriculum, the Pediatric Advanced Life Support guidelines, student surveys, and simulation literature, this educational module uses a hands-on method for teaching and assessing students' approach to pediatric respiratory distress. In the module, the instructor uses high-fidelity simulation to demonstrate the major causes and treatments of pediatric respiratory distress and provides students with the opportunity to apply these principles in a simulated patient experience. This educational module has been successfully implemented as a core learning activity in the pediatrics clerkship at a large US medical school. At the time of publication, more than 250 students have participated in the exercise. Students generally rate the conference as an outstanding experience. On a 5-point Likert scale (1 = strongly disagree, 5 = strongly agree), the mean score associated with the statement "The overall quality of this session was excellent" was 4.87. Prior to the module's initiation, less than half the students completing the pediatrics clerkship reported comfort in their skills assessing an airway issue in a pediatric-age patient. After the first year, more than three-quarters of students reported comfort in the same measure.